The reality construction of wife figure in "suara hati istri" movie on indosiar - Dian Dian; Sisca T. Gurning; Ciptono Setiobudi; Pieter Andrian (The Indonesian Journal of Communication Studies, 2023)
This research is motivated by the reality of married couples living in big cities in Indonesia, presented by television media through soap operas or FTV (Film Televisi/Television Film). The study focuses on FTV Suara Hati Istri on TV Indosiar, which shows social construction and reality in the female character, especially a wife figure. This research examines the FTV Suara Hati Istri episode "Suamiku Membayar Ketulusan Hatiku dengan Pengkhianatan (My Husband Repays My Sincerity with Betrayal)", where Mita is described as a wife who sincerely loves her husband but humiliates her. The purpose of this research is to discover the construction of the character Mita as a wife and the meaning about the reality of a wife. This qualitative research method uses semiotic analysis of the Roland Barthes model with a constructivist paradigm. Moreover, the data are analysed using Berger and Luckman's social construction theory which divides reality into objective, symbolic, and subjective reality. Results showed that the reality of Mita's character as a wife is indeed constructed as a wife who is economically independent and highly educated but weak in the face of her husband's attitude, who is rude, unfaithful, and tends not to respect her as a wife.